Canon Law Historical Background of Categories of the Canonical Singular Administrative Acts - Szuromi, Szabolcs Anzelm (Studia canonica, 2015)
A singular administrative act is a decision bound to ecclesiastical executive power, which creates a right regarding certain individuals. Although according to the law in effect in itself it is not a legal norm; but at first in the matured medieval canon law it was considered as such, later, however, in the footsteps of accurate distinctions made by jurisprudence, it was judged not to be regarded as a legal norm. Singular decision is, right because of its administrative character, not to be mixed up with the decision made in a judicial process — be it contentious or penal —, in spite of the fact, that in many cases the competent ecclesiastical authority’s decision to make an administrative act is in order to avoid trial or to safeguard the reputation of the Church. Singular decree, that is decretum singulare (and its most characteristic kind the singular precept: preceptum singulare), rescript (rescriptum), privilege (privilegium), dispensation (dispensatio), and other acts not forming a separate group, issued by the competent ecclesiastical authority and inserted into the law in effect, had been known also in the earlier law. The singular administrative acts in the Latin canon law in effect, have an old tradition — generally going back to Roman Law —, and the canonical norms relating to them have broadened continuously, especially due to the ecclesiastical legislation of the matured middle ages, and sequentially in the modern age too.